Taxation of Academic Teachers’ Royalties. Controversies in the context of the general interpretation by the Minister of Finance - Świstak, Marzena; Smoleń, Paweł Piotr (Review of European and Comparative Law, 2022)
The Act on Personal Income Tax stipulates a number of methods for calculating costs, which unfortunately often leads to disputes between taxpayers and tax authorities. The same also concerns the rules applicable specifically to academic teachers performing their duties under an employment relationship. Problems emerge both in the context of the manner and scope of eligibility for flat-rate 50% tax-deductible expenses. Notably, the interpretative problems stem not only from the provisions of tax law as such. They also emerge in the context of the higher education reform. But even though the observed legal inconsistencies require urgent legislative action, the necessary amendment to the provisions of the Act of 20 July 2018 – Law on Higher Education and Science has yet to be introduced. Nearly two years after the Act’s entry into force, the Minister of Finance finally decided to issue a general interpretation. Therein, it is stated that in terms of the applicability of 50% tax-deductible expenses, the Act of 20 July 2018 – Law on Higher Education and Science constitutes lex specialis, i.e. ultimately, the 50% cost deduction is applicable to the entirety of an academic teacher’s remuneration. The following paper provides a critical analysis of the present regulations as well as possible solutions to the current fiscal and legal stalemate. In the authors’ opinion, the general interpretation by the Minister of Finance fails to substantially amend the quality of the law whose provisions remain largely unclear. At the same time, its practical value for the academia cannot be denied. Undoubtedly, the fact that the same was issued by the direct superior of tax authorities will make this opinion difficult to ignore in the context of individual cases.